Native T1 mapping for differential diagnosis of left ventricular hypertrophy. (13th July 2021) - Lavall, D; Vosshage, NH; Stoebe, S; Denecke, T; Hagendorff, A; Laufs, U
Abstract: Funding Acknowledgements: Type of funding sources: None. Purpose: The aim of this study was to investigate native T1 mapping cardiac magnetic resonance (CMR) tomography for the differential diagnosis of left ventricular (LV) hypertrophy. Background: Mapping techniques are useful to characterize myocardial tissue abnormalities, particularly cardiac amyloidosis. However, specific cut-off values to differentiate LV hypertrophic phenotypes on 3.0 tesla CMR scanners have not been established, yet. Methods: We retrospectively identified patients in the CMR database of Leipzig university hospital with increased LV wall thickness (≥12mm diameter at end-diastole) who were referred for the evaluation of LV hypertrophy or ischemia between 2017 and 2020 on a 3T scanner (Philips Achieva). Patients with suspected or confirmed myocarditis were excluded. Diagnosis of cardiac amyloidosis was made by either biopsy or non-invasively by bone scintigraphy and screening for monoclonal gammopathy. T1 mapping was measured as global mean value from 3 short axis slices of the LV. Results: 128 consecutive patients were included in the study. 31 subjects without evidence of structural heart disease served as healthy control. The final diagnosis was cardiac amyloidosis in 24 patients (5 patients with light-chain, 18 with transthyretin amyloidosis, 1 undetermined), hypertrophic cardiomyopathy in 24, and hypertensive heart disease in 80 patients. Mean age of patients was 65 ± 13years, 84% were male. LV mass was increased in patients with LV hypertrophy compared to healthy control (p < 0.001). Native T1 values of the LV myocardium were higher in patients with cardiac amyloidosis (1409 ± 59ms, p < 0.0001 vs. all other groups) compared to healthy control (1225 ± 21ms), patients with hypertrophic cardiomyopathy (HCM; 1263 ± 43ms) and hypertensive heart disease (HHD; 1257 ± 41ms) (Figure). Patients with hypertrophic cardiomyopathy and hypertensive heart disease did not differ in their native T1 values, but both groups were increased compared to healthy control (p < 0.01). Receiver operating characteristic analysis of native T1 values demonstrated an area under the curve for the detection of cardiac amyloidosis of 0.9954 (p < 0.0001) vs. hypertrophic cardiomyopathy, hypertensive heart disease and healthy control. The optimal cut-off value was 1341ms, with a sensitivity of 100% and a specificity of 97%. Conclusion: Native T1 mapping has high diagnostic accuracy for the diagnosis of cardiac amyloidosis among patients with LV hypertrophy. These data need confirmation in a prospective clinical trial. Study ID: DRKS00022048